2012
DOI: 10.1373/clinchem.2011.176487
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Requesting of Glycated Hemoglobin (Hb A1c) Is Widespread: Assessment of Prevalence, Impact of National Guidance, and Practice-to-Practice Variability

Abstract: BACKGROUND:Estimates suggest that approximately 25% of requests for pathology tests are unnecessary. Even in diabetes, for which international guidance provides recommended testing frequency, considerable variability in requesting practice exists. Using the diabetes marker, Hb A 1c , we examined (a) the prevalence of under-and overrequesting, (b) the impact of international guidance on prevalence, and (c) practice-to-practice variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 16 publications
7
57
1
2
Order By: Relevance
“…However, we found no previous work examining potential predictors for receiving more frequent annual HbA1c checks in patients with type 1 diabetes, such as those reported here (e.g., CSII and care unit). Recent studies of the frequency of HbA1c measurements in patients with type 2 diabetes or without specifying the type of diabetes, have reported that HbA1c checks are underused in the UK and Australia, without generally examining various predictors for more frequent HbA1c checks [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…However, we found no previous work examining potential predictors for receiving more frequent annual HbA1c checks in patients with type 1 diabetes, such as those reported here (e.g., CSII and care unit). Recent studies of the frequency of HbA1c measurements in patients with type 2 diabetes or without specifying the type of diabetes, have reported that HbA1c checks are underused in the UK and Australia, without generally examining various predictors for more frequent HbA1c checks [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…On top of this hierarchy are assessments of the effect of analytical performance on clinical decision-making (outcome studies), second professional recommendations, third quality specifications laid down by regulation or external quality assessment scheme (EQAS) organizers and last, published data on the state-of-the-art. It is not surprising, that most work for setting quality specifications even lower in hierarchy than HTA or the good use of laboratory medicine (GULM) has been done so far on 'simple chemical tests' such as electrolytes, glucose, or Hb A1c [4] leaving wide areas of laboratory medicine without widely-accepted recommendations [5] and the practical use of these recommendations has not reached the whole area of laboratory medicine due to numerous reasons, most of them not under sufficient control of the people working in the laboratory.…”
Section: Hta and Stockholm Recommendationsmentioning
confidence: 99%
“…Diabetic patients ' participation in disease management programs is also associated with lower medical costs [ 92 ]. A recent paper by Driskell et al highlighted that glycated hemoglobin assays were inappropriately prescribed in 50% of cases [ 93 ], and this justifies the correct use of markers of glycemic control such as HbA 1c for predicting all types of cost-generating complications. This applies to both short-and long-term costs [ 94 ].…”
Section: Diabetes and Laboratory Managementmentioning
confidence: 99%